Global Eradication of Yaws: Neglected Disease with Research Priority (Journal of Medicine, 2009)
Yaws is a disfiguring, debilitating non-venereal treponemal infection caused by Treponema pallidum subspecies pertenue. It is a contagious disease transmitted by direct (person-to-person) contact with the infectious yaws lesion. Early lesions of this disease manifest in the form of skin lesions, which on healing show little scarring. The disease can be progressive wherein bone and cartilage are affected leading to disability. The disease can be cured and prevented by a single injection of long acting (benzathine benzyl) penicillin. Between 1952 and 1964, a worldwide campaign led by WHO and the United Nations Children's Fund (UNICEF) to control and eventually eradicate yaws and other endemic treponematoses were undertaken.By the end of the 1970s, reemergence of yaws occured in many countries and it prompted a World Health Assembly Resolution requesting the implementation of integrated treponematoses control programmes. While the programme initially showed tremendous result but yaws control efforts paved the way for the development of the primary healthcare system in affected areas. The disease is amenable to eradication epidemiologically, technologically, historically and from political point of view if appropriate research based programme in national and international arena is set. Key words: Eradication, Yaws, Neglected,disease,Research   doi: 10.3329/jom.v10i2.2825   J MEDICINE 2009; 10 : 109-114